Inhibitory Effect of the Hybrid Bacteriocin Ent35-MccV on the Growth of Escherichia coli and Listeria monocytogenes in Model and Food Systems - Acuña, Leonardo (2015)
Bacteriocins are being used as new food biopreservative agents. In general, bacteriocins produced by Gram-positive bacteria are active against other Grampositive. Basically, the same principle applies to those produced by Gram-negative bacteria. They have a restricted spectrum of action against related bacteria to those that produce the bacteriocin. Therefore, other hurdles or chemical preservatives are necessary to apply to broaden the spectrum of action of bacteriocins in foods. This is a further and deeper study of the possible application of the hybrid wide-spectrum bacteriocin named Ent35-MccV in food. Its antimicrobial activity was assayed in skim milk and patties as food models against Listeria monocytogenes and Escherichia coli. The influence of the temperature and digestive proteases on its biological activity and its antimicrobial activity was tested in vitro on a variety of pathogenic and food spoilage bacteria. The results showed that Ent35-MccV could inhibit the growth of both the Grampositive L. monocytogenes and the Gram-negative E. coli in model food, and its activity was not affected by heating conditions including autoclaving. E. coli strains and Listeria spp. are the most affected bacteria, but Ent35- MccV showed antimicrobial activity against some strain of Salmonella spp., Staphylococcus epidermidis, Enterobacter aerogenes, Morganella morgani, Proteus mirabilis, Shigella boydii, Shigella flexneri, and Shigella sonnei.